Industrial Application of Chitosan as Promising Material for Wastewater Purification: A Review - Belgis, Belgis (Universitas Indonesia, 2020)
The rapid growth of the industry is giving positive effects for humans by providing daily needs and supporting economic development. However, the industrial process also releases pollution to the environment, which can cause water scarcity, biodiversity loss, and climate change. Removing these pollutants from various industrial wastes is a requirement for ensuring proper water quality for human consumption, agricultural use, and environmental safety. This work aims to explain the use of natural resources as a source of valuable compounds that can be used in wastewater treatment, particularly in Indonesia, by adopting a literature study method reviewing both national and international references. Chitosan is an effective bio-absorbent pollutant because of its high level of deacetylation and free amino groups, making it polycationic which is capable of being bound to metals, proteins, and dyes. Chitosan membranes can be applied only with chitosan material and composites: chitosan-Polyethylene Glycol (PEG), chitosan-Poly Vinyl Alcohol, chitosan-biosilica, chitosan-PVA-silica, chitosan-alginate, chitosan-cellulose, and chitosan-silica. Chitosan has the ability as a coagulant and reducing water turbidity. Chitosan can absorb metal ion (Cr (VI), Cs+, Pb(II), Fe, Cu(II)), dyes (anthraquinone dyes, brilliant blue, yellow dye, methylene blue, disperse orange, disperse blue, rhodamine B), drug residue, and hazardous materials, and can be used as raw material or in a film form. Since there is a high abundance of chitosan raw material in Indonesia, it is supposed to be able to support the application of chitosan as a natural purifying agent considering its high ability to absorb heavy metal and some dangerous materials.